A latent profile analysis of subjective exercise experiences among physically vulnerable college students and psychiatric symptoms correlates during three phases of the COVID-19 pandemic in Wuhan, China - Li, Jinglin; Xiao, Ming; Huang, Hongyuan; Liu, Huinan (Frontiers in Psychology, 2023)
Physical activity among college students since COVID-19 was well studied, however subjective exercise experience, the emotional response towards physical exercise received little attention, not to mention the subgroups within the heterogeneous group. The present study used latent profile analysis (LPA) to explore the latent class of subjective exercise experience among physically vulnerable college students who scored 59 points or less in tests under the National Student Physical Health Standard. Three non-duplicated samples at different stages of COVID-19 were collected in March 2020 (N=127), March 2021 (N=118), and November 2021 (N=206) respectively. Psychometrically validated scales, namely Subjective Exercise Experiences Scale (SEES), Generalized Anxiety Disorder (GAD-7), and Patient Health Questionnaire (PHQ-9) were used to measure subjective exercise experience, anxiety symptoms, and depressive symptoms. Latent profile analysis revealed a three-class solution for subjective exercise experience of physically unfit students, namely “negative experience group” (30.82%), “fatigue group” (41.91%), and “positive experience group” (27.27%). Multinominal regression showed that probable anxiety (OR=0.12) was associated with overall negative exercise experience while probable depression (OR=0.19) was associated with psychological fatigue. Females (OR=0.496) were more likely to experience overall negative exercise experience, and the outbreak of COVID-19 (OR=2.14) influenced the psychological distress of subjective exercise experience compared with the other two phrases in post-COVID-19 era. Our findings provided significant implications for physical education targeting at university students that interventions should be tailored differently for three profiles of subjective exercise experience.